2010
DOI: 10.1177/0969733010361445
|View full text |Cite
|
Sign up to set email alerts
|

Research on ethics in nursing care for older people: A literature review

Abstract: The aim of this review was to analyse the empirical studies that focus on ethics in nursing care for older people, scoping the need and areas for further study. A search of the MEDLINE and CINAHL databases (earliest to August 2009) was conducted using the the keywords: ethic* and nursing or care or caring and elderly or aged or older. After a four-stage process, 71 empirical articles were included in the review, with informants ranging from elderly people to relatives, caregivers, managers and students in care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 73 publications
1
64
0
2
Order By: Relevance
“…The findings of this study also underpin the importance of strengthening the moral and ethical awareness of healthcare professionals in NHs. 6,9,18,[20][21][22][23] The daily ethical challenges encountered in NHs require that nurses can reflect critically on their actions. The moral competence of nurses might develop, and moral difficulties may be avoided, if challenging situations are the subjects of critical reflection and review in the NH.…”
Section: Interaction and Decision-making Processesmentioning
confidence: 99%
“…The findings of this study also underpin the importance of strengthening the moral and ethical awareness of healthcare professionals in NHs. 6,9,18,[20][21][22][23] The daily ethical challenges encountered in NHs require that nurses can reflect critically on their actions. The moral competence of nurses might develop, and moral difficulties may be avoided, if challenging situations are the subjects of critical reflection and review in the NH.…”
Section: Interaction and Decision-making Processesmentioning
confidence: 99%
“…The main focus in the literature seems to be on the patient’s right to be informed and take part in decisions concerning medical treatment and end-of-life care [3, 14, 15, 1820]. In the present study, theory on family ethics has been useful to sensitize our understanding of the complexity of ACP-conversations, and we ask whether family ethics perspectives may strengthen the nursing home patients’ possibilities to get his or her values and preferences known or expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals in community care experience many and important ethical dilemmas [9, 13, 15, 16]. Van der Dam et al reviewed the literature on ethics support in institutional elderly care and identified 60 papers [10].…”
Section: Introductionmentioning
confidence: 99%